Climate change and effectiveness of dams in flood mitigation in India - Urmin Vegad; Vimal Mishra (npj Natural Hazards)
Abstract India, the third-largest dam-building nation, highly relies on dams for irrigation, hydropower, and flood control. Observations show that dams both mitigated and triggered floods across Indian river basins. However, their effectiveness in mitigating floods under current and future climates remains unknown. Using in-situ and satellite observations and model simulations for 178 major dams, we show that flood mitigation depends more on antecedent reservoir storage than upstream rainfall. Downstream floods are more likely when reservoirs exceed 90% of their full capacity. The duration with reservoir storage exceeding 90% is projected to increase threefold at 3 °C warming compared to 1 °C. A substantial rise in compound events of high inflow and high antecedent reservoir storage is also projected from 0.55 ± 0.22 events/year at 1 °C warming to 1.1 ± 0.4 events/year at 3 °C warming. Our findings highlight the need for advanced approaches for dam operations (maintaining buffer storage) integrated with early warnings of extreme inflow in India.